Adaptation to Spanish population an instrument of moral judgments: Moore’s battery of moral dilemmas - Carmona-Perera, Martina; Caracuel, Alfonso; Verdejo-García, Antonio; Perez-García, Miguel (Anales de Psicología / Annals of Psychology, 2013)
The cognitive and emotional neuropsychological processes underlying moral judgments are the focus of groundbreaking research in understanding moral cognition.  The aim of this study is to adapt to Spanish the moral dilemmas battery of Moore. This battery presents a set of moral dilemmas from a utilitarian choice (assuming an emotionally aversive behaviour for a higher benefit) and a non-utilitarian choice. The study involved 154 university students who were given the Spanish version of Moore’s battery. We researching three types of dilemmas: moral-personal (oneself performs the aversive action, increasing the emotional charge), impersonal-moral (the action is carried out indirectly, decreasing the emotional charge) and non-moral. The dependent variables were the proportion of affirmative answers, which reflect utilitarian choices, and the perceived difficulty to produce the judgments. The results showed good psychometric properties and significant differences in the proportion of affirmative answers and the difficulty depending on the type of dilemma, the moral-personal dilemmas generated fewer utilitarian choices and judgments with more difficulty. In conclusion, the Spanish version of Moore's battery allows measuring reliably the moral judgments, discriminating between different patterns of choice depending on the emotional charge, so it is postulated as a potentially useful instrument for assessing populations with impaired decision-making related to emotional processing